The Role of LNG in the Transition Toward Low- and Zero-Carbon Shipping - Englert, Dominik; Losos, Andrew; Raucci, Carlo; Smith, Tristan (World Bank, Washington, DC, 2021)
Due to its much lower air pollution and potential greenhouse gas (GHG) emissions benefits, liquefied natural gas (LNG) is frequently discussed as a fuel pathway towards greener maritime transport. While LNG’s air quality improvements are undeniable, there is debate within the sector as to what extent LNG may be able to contribute to decarbonizing shipping. This report, “The Role of LNG in the Transition Toward Low- and Zero-Carbon Shipping,” considers the potential of LNG to play either a transitional role, in which existing LNG infrastructure and vessels could continue to be used with compatible zero-carbon bunker fuels after 2030, or a temporary one, in which LNG would be rapidly supplanted by zero-carbon alternatives from 2030. Over concerns about methane leakage, which could diminish or even offset any GHG benefits associated with LNG, and additional capital expenditures, the risk of stranded assets as well as a technology lock-in, the report concludes that LNG is unlikely to play a significant role in decarbonizing maritime transport. Instead, the research finds that LNG is likely to only be used in niche shipping applications or in its non-liquefied form as a feedstock to kickstart the production of zero-carbon bunker fuels when used in conjunction with carbon capture and storage technology. The research further suggests that new public policy in support of LNG as a bunker fuel should be avoided, existing policy support should be reconsidered, and methane emissions should be regulated.